Early Growth of Acacia mangium × Acacia auriculiformis Hybrid in a Clonal Test at Three Different Sites in Indonesia - Sunarti, Sri; Budiyansah, Budiyansah; Nirsatmanto, Arif (Jurnal Manajemen Hutan Tropika, 2018)
Abstract Acacia mangium × Acacia auriculiformis hybrid is a promising new option for forest plantations that is propagated using clonal technologies. However, its deployment must be supported by an understanding f how clones respond to differing environment conditions. A multi-site test is therefore necessary; in this study, three sites, one in Central Java, and one each in Riau and Jambi were used. Between 20 and 44 clones were used at each site, and nine were common to each site. Each trial was laid out in a randomized complete block design with between four and 20 replications, and a between-tree spacing of either 3 × 3 m or 3 × 2 m. Height (H), diameter at breast height (D) and volume (V) were measured two years after planting. Growth rates in Riau and Jambi were substantially higher than in Central Java, a difference that can be attributed to soil type and rainfall. Significant differences were found among the clones for all these variables at all the three sites. For the three sites, clone repeatability was high and ranged from 0.91 to 0.97; ramet repeatability was moderate and ranged from 0.49 to 0.59. Clone x site interaction was highly significant in all parameters observed. For the nine common clones, multi-site clone repeatability was also high (0.93-0.96), but ramet repeatability was low (0.26-0.35). The best performing clones were Clones 4, 6 and 44. However there were differences in ranking, and only Clone 44, in Central Java and Riau, was the best performing. The experiment has shown the importance of these trials for developing strategies for deploying clonal stock. However the results suggest that it will take longer than two years for a clear pattern of differences between clones to emerge. Keywords: new variety, clone, repeatability, multi-site